PELAKSANAANKBAT DALAM PENGAJARAN DAN PEMBELAJARAN PENDIDIKAN ISLAM SEKOLAH MENENGAH: SATU TINJAUAN DI PUTRAJAYA - Nor, Norasmahani Hj; Suhaimi, Nur Sofiah; Abdul Wahab, Nur Syamira; Che Ismail, Mohd Khushairi; Che Noh, Mohd Aderi; Razak, Khadijah Abdul (Proceeding 7th International Seminar on Regional Education, 2015)
Abstract The application of higher-order thinking skills (HOTS) is one of the countrys educational aspirations to create a generation that is able to compete globally. Realising its importance, this research was conducted to identify the implementation of HOTS in teaching and learning (T&L) Islamic Education.Respondentsâ for this study consisted of 20 Islamic Education teachers of secondary schools in Putrajaya. Data were analyzed using the Statistical Package for Social Science (SPSS) software. Results showed that the implementation of HOTS in management and administration, understanding HOTS in the process of T&L and teaching HOTS implementation are at a moderate level. While understanding HOTS planning in the process of T&L, understanding construction HOTS items and understanding evaluation of HOTS are on a high level. The implications of this study found that teachers need to be given more exposure through courses, workshops and in-service training so that generating HOTS among students will be successfully implemented.Keywords: higher order thinking skills, teaching and learning, IslamicEducation, implementation, understanding, planning, evaluation.